2023
DOI: 10.1021/acs.est.3c05041
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Bacteriophages: New Directions in Environmental Biocolloid Research

Ethan Hicks,
Nicholas M. K. Rogers,
Christine Ogilvie Hendren
et al.

Abstract: There is a long-standing appreciation among environmental engineers and scientists regarding the importance of biologically derived colloidal particles and their environmental fate. This interest has been recently renewed in considering bacteriophages and extracellular vesicles, which are each poised to offer engineers unique insights into fundamental aspects of environmental microbiology and novel approaches for engineering applications, including advances in wastewater treatment and sustainable agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 182 publications
0
1
0
Order By: Relevance
“…In urban rivers, microorganisms exchange genetic material and molecular information via EVs 19 , aiding diverse species to adapt and survive challenging environments [20][21][22][23] . The transfer of EV cargo can increase the genetic diversity of microorganisms 24,25 , which may enhance their ability to withstand pollutants and other stressors commonly encountered in urban waterways 26 . Early studies have demonstrated that Prochlorococcus, a prevalent marine cyanobacterium, releases EVs containing proteins, DNA, and RNA.…”
Section: Introductionmentioning
confidence: 99%
“…In urban rivers, microorganisms exchange genetic material and molecular information via EVs 19 , aiding diverse species to adapt and survive challenging environments [20][21][22][23] . The transfer of EV cargo can increase the genetic diversity of microorganisms 24,25 , which may enhance their ability to withstand pollutants and other stressors commonly encountered in urban waterways 26 . Early studies have demonstrated that Prochlorococcus, a prevalent marine cyanobacterium, releases EVs containing proteins, DNA, and RNA.…”
Section: Introductionmentioning
confidence: 99%